Work-related musculoskeletal pain and its self-reported impact among practicing dentists in Puducherry, India - Kuldeep Singh Shekhawat; Arunima Chauhan; S Sakthidevi; Basavaraj Nimbeni; Shruthi Golai; Lincy Stephen (Wolters Kluwer Medknow Publications, 2020)
Background: Work-related musculoskeletal pain (MSPs) is not uncommon among dentist and often limits their work efficiency impacting their quality of life. Aim: The present research was conducted to identify site-specific pain resulting from musculoskeletal disorders (MSDs) among practicing dentists and determine its impact on their quality of life. Setting and Design: A cross-sectional questionnaire study conducted among practicing dentists of Puducherry Taluk, Puducherry, India. Method and Materials: A closed-ended, self-administered questionnaire was distributed to 95 practicing dentists to identify site-specific MSP from the study subjects. Data on pain due to MSDs, frequency of pain, its impact on quality of life, relieving factors, patients attended per day, working hours per day, and awareness on ergonomics were also recorded. Statistical Analyses: The data were analyzed for descriptive statistics, and Chi-square tests was used for proportions. Results: Almost all respondents experienced pain due to MSDs. Approximately, 11.1% "always" experienced elbow pain; 5.6% "always" experienced pain in neck and back. Approximately, 83% "sometimes" experienced pain in the back. Pain in elbow was significantly associated with gender (P = 0.036), qualification (P = 0.029), and years of practice (P = 0.032). Approximately, 36% reported having an impact on their life. Conclusion: The magnitude of the problem is slowly shifting from "sometimes" to "always." Although small in proportion, pain due to MSDs has an impact on dental practitioners' quality of life, and elbow pain was reportedly higher in the study setting. Measures need to be implemented before MSD becomes a career limiting occupational hazard.